Sexual minority substance use disparities: Bisexual women at elevated risk relative to other sexual minority groups - Schuler, Megan S. (Drug Alcohol Depend, 2019)
BACKGROUND: Prior studies characterizing sexual minority substance use disparities have primarily compared lesbian/gay and bisexual individuals, respectively or in combination, to heterosexual individuals. In light of emerging evidence that bisexual individuals may have particularly elevated substance use risk, we examine differences in recent substance use between bisexual and lesbian/gay individuals using national survey data. METHODS: Data on 126,463 adults (including 8,241 LGB adults) were from the 2015-2017 National Survey on Drug Use and Health. Substance use outcomes included binge drinking, cigarette smoking, cigar smoking, marijuana use, illicit drug use, opioid misuse, alcohol use disorder, nicotine dependence, and substance use disorder. Logistic regression was used to estimate sexual identity- and gender-specific odds ratios, controlling for demographic characteristics. Of particular interest were estimates comparing bisexual and lesbian/gay individuals of the same gender. RESULTS: Both male and female sexual minority adults had significantly elevated rates of substance use compared to heterosexual adults. Furthermore, relative to lesbian/gay women, bisexual women had significantly elevated odds of binge drinking (aOR=1.29), marijuana use (aOR=1.42), illicit drug use (aOR=1.55), opioid misuse (aOR=1.53) and alcohol use disorder (aOR=1.48) . Relative to gay men, bisexual men had significantly elevated cigar use (aOR=1.64). CONCLUSIONS: Bisexual women were at significantly greater risk for multiple substance use behaviors relative to lesbian/gay women. We did not observe any substance use behaviors for which bisexual individuals had significantly lower risk than their lesbian/gay peers. These disparities may be explained, in part, by unique risk factors for substance use experienced by bisexual individuals, particularly bisexual women.